The Rising Share of Part-time Employment - Parsons, Stephanie; Cassidy, Natasha (My University, 2017)
One of the most significant changes to the Australian labour market in recent decades has been the rise in the share of part-time employment to account for nearly one-third of total employment. This article details the various supply and demand factors that have underpinned the increase in part-time employment, as well as some of the characteristics of part-time workers. Because there are some part-time workers who want to work additional hours, it is useful to consider underemployment as well as unemployment in measuring labour market spare capacity.
September Quarter Bulletin
Bulletin
Keywords: Employment -- Labour Markets; Employment -- Underemployment; Employment -- Labour force supply; Employment -- Security of employment; Employment -- Hours; Employment -- Labour force participation; Labour market; Employment; Underemployment; Labour Markets; Labour force participation; Labour force supply; Security of employment; Hours; Employment and unemployment